A study on role of consumer generated media in influencing consumer buying behaviour with reference to electronic devices - Galla Lavanya; Y, Subbarayudu (Journal of Management and Science, 2022)
The aim of the study is to understand the role of Consumer Generated Media in influencing consumer’s behaviour by utilising consumer decision-making process towards electronic devices. The study mainly focused on high complex purchases, which are characterised by high consumer involvement and prominent brand differences.The study relied on techno-savvy consumers’ from four districts of Rayalseema zone via online survey.Data from a sample of 120 respondents had taken and applied SPSS for analysis. Results shown that consumer generated media shows much impact on consumer decision- making process mainly at the stages of information search and alternative evaluation.